KESAMBI (Schleichera oleosa (Lour) Oken) TREE BARK EXTRACT AND ITS FRACTIONS: PHYTOCHEMICAL SCREENING, DETERMINATION OF TOTAL PHENOLIC CONTENT, AND ANTIMICROBIAL ACTIVITY AGAINST Staphylococcus aureus, Escherichia coli, AND Candida albicans - Masduqi, Ahmad Fuad; Purwaningsih, Yuliana; Salsabila, Karisma Putri; Ma’arif, Mohammad Naufal Syahrul (Berita Biologi, 2025)
Microorganisms are becoming increasingly resistant to antibiotics, creating a pressing need for new therapeutic agents to address this issue. One plant that shows promise as an antimicrobial is kesambi (Schleichera oleosa (Lour) OKEN). This plant is commonly used in traditional medicine to treat skin infections. This research set out to identify the secondary metabolites in ethanol extract and fractions of kesambi stem bark and their antimicrobial activity against S. aureus, E. coli, and Candida albicans. Bioactive compounds were extracted through maceration with 96% ethanol, resulting in a concentrated extract yielding 22.34 ± 1.44%. The concentrated extract was gradually separated using n-hexane and ethyl acetate, yielding n-hexane fraction, ethyl acetate fraction, and aqueous fraction of 1.84 ± 0.82%, 16.46 ± 4.90 %, and 40.74 ± 6.27%, respectively. Phytochemical screening of each fraction and extract was carried out using color reagents and ATR-FTIR spectrometry. According to the profiling, the extracts and fractions contain phenolic compounds, flavonoids, alkaloids, steroids, saponins, triterpenoids, glycosides, and tannins. The FTIR analysis provided valuable insights into the presence of different functional groups, including -OH, C=O, CH3, C=C, and C-O esters. Antimicrobial activity was tested using the well diffusion method. The extract displays a more significant inhibition zone against E. coli and Candida albicans when compared to both the ethyl acetate fraction and the aqueous fraction. However, the ethyl acetate fraction demonstrates a larger inhibition zone against S. aureus than both the extract and the aqueous fraction. This suggests a promising potential for these samples to combat these pathogens.